Methodological quality of Grounded Theory research with families living with chronic illness - Mayckel da Silva Barreto; Cristina Garcia-Vivar; Sonia Silva Marcon (Elsevier, 2018)
Aim: The aim of this study was to assess the methodological quality of Grounded Theory (GT) studies related to families living with chronic illness, and the extent to which the common methodological elements of GT are being attended to by researchers. Method: Systematic review. Four databases were searched for GT studies, published between 2010 and 2015. To assess the methodological quality of the studies, seven elements of rigor were identified: constant comparative analysis, coding process, theoretical sampling, theoretical data saturation, memos, diagram and central category/theoretical model. Results: Of the forty-seven articles included, twenty-four (51.0%) were classified as excellent, fifteen (31.9%) as fair and eight (17.1%) as poor. Most articles used the constant comparative analysis (93.5%), coding process (91.3%), theoretical data saturation (85.0%) and the development of central category or theoretical model (80.7%). However, only thirty-four studies (72.3%) presented diagrams, thirty-three (70.2%) used theoretical sampling, and thirty studies (63.7%) reported having used memos. Conclusion: This review updates the state of the art about the methodological quality of GT research with families living with chronic illness and it highlights the need for consensus regarding the methodological elements to be described in GT studies in family nursing. Keywords: Methodological quality, Grounded Theory research, Systematic review, Chronic illness, Family nursing